Food Vertigo. Processes and devices for metropolitan food resilience - Filippo Orsini (Techne, 2022)
By 2050, more than 80% of the world’s population will live in metropolitan conurbations. From a holistic and circular economy perspective, strategies for urban resilience that include universal access to food and alimentary security will be essential. This paper investigates the integration of existing traditional urban farming systems with new vertical farming techniques. The proposal is for an infrastructural strategy that improves human-environment interaction through the development of agricultural production on an intermediate scale and through architectural elements – such as urban vertical farms – configured as modular landmarks that respond to the technological complexity of the agro-industrial chain and can be adapted to different contexts, thus defining an inclusive and sustainable urban landscape.